evaluation of efficiency of laminated alginate impression in the upper partial denture fabrication - خيربك عامر; محمود محمود (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: The success of Removable Prosthodontics depends on the accuracy of the impressions, and therefore the need for a secondary impression has always been after the Primary impression, adjusting the thickness of the impression material. Usually we take the First impression with alginate and the Secondary with alginate as well, but after making an individual tray that fulfills the thickness requirement. In this paper, we presented an alternative method for registering a Secondary impression in the Very first visit by modifying the tray. Objective: To evaluate the dimensional stability of the laminated alginate impression in comparison with the primary impression taken by alginate, and a secondary impression Custom tray MATERIALS AND METHODS: The example of epoxy was used as a Control model, and 30 impression of this example were recorded, divided as follows, 10 impression with the stock tray as group A, And 10 were taken with custom tray as group B, And 10 were taken with the Laminated alginate technique as group C. The impressions were taken using a special plunger that simulated the patient’s mouth. After the impression were taken, dimensional change was numerically measured and statistical tests were performed to compare between groups. Results: There are no statistical differences between the three groups in terms of dimensional change, by comparing group A with group C, and group B with group C. Conclusions: The laminated alginate impression gives good laboratory results and is similar in terms of dimensional accuracy compared to the conventional impression and the custom tray impression.